Fluxos de informação e linguagem em ambientes organizacionais - Valentim, Marta Lígia Pomim [UNESP]; Teixeira, Thiciane Mary Carvalho (My University, 2012)
Information flows are formed naturally or formally induced in organizational settings, passing from the strategic level to operational level, reflecting, and impacting in the processes that make up the organization, including the decision-making process and therefore the action strategies of organization. The management of organizational environments based on information requires careful attention to various kinds of languages used for communication between sectors and employees of the organization, whose goal is to share, disseminate and socialize the information produced in this environment.
Flows of information and language in organizational settings
Keywords: Formal and informal channels; Formal and informal language flows; Information flows; Organizational environments; Organizational jargon